Response and recovery of the Comanche carbonate platform surrounding multiple Cretaceous oceanic anoxic events, northern Gulf of Mexico. (May 2015) - Phelps, Ryan M.; Kerans, Charles; Da-Gama, Rui O.B.P.; Jeremiah, Jason; Hull, David; Loucks, Robert G.
Abstract: The ubiquity of carbonate platforms throughout the Cretaceous Period is recognized as a product of high eustatic sea-level and a distinct climatic optimum induced by rapid sea-floor spreading and elevated levels of atmospheric carbon-dioxide. Notably, a series of global oceanic anoxic events (OAEs) punctuate this time-interval and mark periods of significantly reduced free oxygen in the world's oceans. The best records of these events are often from one-dimensional shelf or basin sections where only abrupt shifts between oxygenated carbonates and anoxic shales are recorded. The Comanche Platform of central Texas provides a unique opportunity to study these events within a well-constrained stratigraphic framework in which their up-dip and down-dip sedimentologic effects can be observed and the recovery of the platform to equilibrium states can be timed and understood. Stable isotope data from whole cores in middle Hauterivian through lower Campanian mixed carbonate-siliciclastic strata are used to construct a 52-myr carbon isotope reference profile for the northern Gulf of Mexico. Correlation of this composite curve to numerous global reference profiles permits identification of several anoxic events and allows their impact on platform architecture and facies distribution to be documented. Oceanic anoxic events 1a, 1b, 1d, and 2 occurred immediately before, after, or during shale deposition in the Pine Island Member, Bexar Member, Del Rio Formation, and Eagle Ford Group, respectively. Oceanic anoxic event 3 corresponds to deposition of the Austin Chalk Group. Platform drowning on three occasions more closely coincided with globally recognized anoxic sub-events such as the Fallot, Albian-Cenomanian, and Mid-Cenomanian events. This illustrates that the specific anoxic event most affecting a given carbonate platform varied globally as a function of regional oceanographic circumstances. Using chemo- and sequence-stratigraphic observations, a four-stage model is proposed to describe the changing facies patterns, fauna, sedimentation accumulation rates, platform architectures, and relative sea-level trends of transgressive-regressive composite sequences that developed in response to global carbon-cycle perturbations. The four phases of platform evolution include the equilibrium, crisis, anoxic, and recovery stages. The equilibrium stage is characterized by progradational shelf geometries and coral-rudist phototrophic faunal assemblages. Similar phototrophic fauna typify the crisis stage; however, incipient biocalcification crises of this phase led to retrogradational shelf morphologies, transgressive facies patterns, and increased clay mineral proportions. Anoxic stages of the Comanche Platform were coincident with back-ground deposition of organic-rich shale on drowned shelves and heterotrophic fauna dominated by oysters or coccolithophorids. Eustatic peaks of this stage were of moderate amplitude (∼30 m), yet relative sea-level rises were greatly enhanced by reduced sedimentation rates. In the recovery stage, heterotrophic carbonate factories re-established at the shoreline as progradational ramp systems and sediment accumulation rates slowly increased as dysoxia diminished. Full recovery to equilibrium conditions may or may not have followed. Geochemical and stratigraphic trends present in the four stages are consistent with increased volcanism along mid-ocean ridges and in large-igneous provinces as primary drivers of Cretaceous OAEs and the resulting transgressive-regressive composite sequences. Highlights: Oceanic anoxic events 1a, 1b, 1d, 2, and 3 are found in the Comanche Platform in the Gulf of Mexico. These events are associated with carbonate platform drowning and shale deposition, except OAE 3. Stages of drowning and recovery of the platform are equilibrium, crisis, anoxic, and recovery. Organic-rich shale deposition and clay influx began prior to OAEs 1a, 1b, and 2.